Glutathione as an antidote for sulfur mustard poisoning: Mass spectrometric investigations of its potency as a chemical scavenger. (1st September 2018) - Siegert, Markus; Kranawetvogl, Andreas; Thiermann, Horst; John, Harald
Highlights: Sulfur mustard (SM) is a banned blister agent for which no causal therapy exists. An in vitro assay was used to characterize the scavenging potential toward SM. SM-induced alkylation of albumin is a measure of scavenging efficacy. Glutathione did not show a relevant chemical scavenging effect toward SM. Abstract: The banned chemical warfare agent sulfur mustard (SM) still represents a serious threat to civilians and military personnel. Therefore, identification of antidotes and scavengers is of high concern. One promising substance is glutathione (GSH). GSH is known to mitigate symptoms of SM poisoning in vitro and in vivo . However, the mechanism of action remains unclear with respect to physiological impact as well as chemical scavenging by reaction between GSH and SM. Therefore, a novel in vitro method was used to characterize the scavenging potential of GSH. Accordingly, alkylation of human serum albumin (HSA), which represents an established biomarker for SM intoxication, was used as a measure for remaining SM. Coincubation of GSH and SM in human serum was performed, and time-dependent degradation of SM was monitored in the presence and absence of GSH. Protein-derived and small molecular reaction products between GSH, HSA, and SM were analyzed using microbore liquid chromatography-electrospray ionization high-resolution tandem-mass spectrometry. Although covalent modification of GSH by SM was observed, measurements clearly documented no significant reduction of SM concentration in the presence of GSH. Accordingly, beneficial therapeutic mechanisms of GSH in the case of SM poisoning would appear to be based on physiological effects than on chemical scavenging.